Community of Ownership of Learning (Global Journal of Human-Social Science, 2013)
New model of teaching and learning was introduced in our school to meet the needs of our students who seek greater autonomy connectivity as well as opportunities for socio-experiential learning The Connected Learning Pedagogy CLP was designed to mine the learning potential of the new social and digital media domain to create a community of ownership of learning promoting collaboration and connectedness among students lecturers and parents To support the implementation of CLP laboratories were equipped with computers and tablet PCs Through them students were connected to various social and digital media such as Facebook Moodle YouTube and iDe Lite ITE video portal to conduct their required research and learning The tablet PCs provided lecturers with the added advantage of mobility during lessons allowing them to facilitate the learning process with ease Students were engaged in many exciting ways through Apps in the tablet PCs In addition parents were connected to students learning through PRISM ITE Parents Real-time Information System on Mobile With the mobile apps PRISM parents are connected to realtime data on their child s learning
Keywords: connected learning; collaboration; digital media; tablet pc; connectedness; ownership of learning; engaging parents